Interpersonal communication relating to others - Beebe, Steven A.; Beebe, Susan J.; Redmond, Mark V.; Terri M. Geerinck (Toronto, Ontario Pearson Custom Publising, 2004)
It includes index.
Keywords: Interpersonal communication